Syriana - Gaghan, Stephen; Clooney, George; Damon, Matt.; Wright, Jeffrey; Cooper, Chris, 1951-; Hurt, William; Elswit, Robert; Desplat, Alexandre; Baer, Robert; Warner Bros. Pictures (1969- ); Participant Productions; 4M (Firm); et al. (Burbank, CA : Warner Home Video, 2006)
A politically charged thriller that unfolds against the intrigues and corruption of the global oil industry. From the players brokering back-room deals to the men toiling in the oil fields, the film illuminates the consequences of the pursuit of power.
English track: Dolby digital 5.1.
Based on the book "See no evil" by Robert Baer.
Originally released as a motion picture in 2005.
Special features: additional scenes; 'Make a change, make a difference' featurette; conversation with George Clooney.
Director of photography, Robert Elswit ; editor, Tim Squyres ; music, Alexandre Desplat ; production designer, Dan Weil.
George Clooney, Matt Damon, Jeffrey Wright, Chris Cooper, William Hurt, Mazhar Munir, Tim Blake Nelson, Amanda Peet, Christopher Plummer, Alexander Siddig.
Keywords: United States. -- Central Intelligence Agency -- Drama; Brokers -- Drama; Corporate lawyers -- United States -- Drama; Oil industries -- Drama; Teenagers -- Pakistan -- Drama; Thrillers (Motion pictures, television, etc.); Suspense films; Films for the hearing impaired